Appropriation scripturale et subversive de l'espace urbain à São Paulo - Timothée Engasser (Les Cahiers de Framespa)
This article explores, from a sociological point of view, a tag movement from São Paulo, the pixação, almost restricted to the only Big São Paulo. Written form's originality and the habits of pixadores are very unique, and this will be very interesting to understand what this movement put at stake in this town, and identify which paradigms are involved within this controversial practice. To do so, we will try to illustrate a movement from actor's points of views, with the help of several interviews. Questioning private property, a certain form of resistance against the increase of social segregation and also the violence of today's Brazil, these are so many themes that are matching up with the pixação of São Paulo. In its originally illegal and subversive form, we are going to question the evolutions of a movement that is entering, little by little, in a process of artification.